COMPONENTS OF PUBLIC POLICY IN THE FIELD OF SUSTAINABLE ECONOMIC DEVELOPMENT - Kharchenko, Oleksiy (Global Prosperity, 2021)
The article examines the features of sustainable development in Ukraine. The goals of sustainable development in the works of scientists and their impact on public policy, in particular: economic goals, social goals, environmental goals. The goals of sustainable development, which are due to geopolitical, geographical, demographic, socio-economic and environmental characteristics, namely: economic growth, environmental protection, welfare, justice, efficient (sustainable) use of natural resources, population stabilization, education. The essence and main content components of the management system of sustainable development of the state, region, enterprise are determined. The types of public policy that are being transformed in the context of ensuring sustainable development of the economic system are identified. Conceptual approaches to the improvement of the state policy system by regional development and its implementation in the context of the state policy of sustainable regional development are offered. The priority spheres of dissemination of public policy in the field of sustainable development in the spheres: spheres of use of natural resources, spheres of environmental pollution, spheres of economic activity, spheres of social development, legal spheres are determined. The application of mechanisms for the implementation of public policy in the field of sustainable development is proposed. Conceptual approaches to the improvement of the state policy system by regional development and its implementation in the context of the state policy of sustainable regional development are developed.